Acoustic radiation force impulse imaging (ARFI) for differentiation of benign and malignant thyroid nodules—A meta-analysis. Issue 11 (November 2015) - Zhan, Jia; Jin, Jia-Mei; Diao, Xue-Hong; Chen, Yue
Highlights: A meta-analysis of acoustic radiation force impulse imaging (ARFI). Differential diagnosis of benign and malignant thyroid nodules. The advantages and limitation of ARFI in thyroid nodules. ARFI has high sensitivity and specificity in the work-up of thyroid nodules. Abstract: Objectives: Work-up of thyroid nodules remains challenging. Acoustic radiation force impulse imaging (ARFI)-generated shear wave elastography, which can measure quantitatively tissue stiffness (virtual touch tissue quantification) is used as a complement to conventional sonography for improving the diagnosis of thyroid nodules. This meta-analysis was performed to expand on a previous meta-analysis to assess the diagnostic power of ARFI in differentiating benign and malignant thyroid nodules. Methods: The MEDLINE, PubMed, SpringerLink databases up to December 31, 2014, were searched. The pooled sensitivity, specificity, and summary receiver operating characteristic curve were obtained from individual studies with a random effects model. Results: Sixteen studies that included a total of 2436 nodules in 2147 patients for ARFI studies were analyzed. The overall mean sensitivity and specificity of ARFI for differentiation of thyroid nodules were 0.80 (95% confidence interval [CI], 0.73–0.87) and 0.85 (95% CI, 0.80–0.90), respectively. A significant heterogeneity was found for both sensitivity and specificity of the different studies ( P  < 0.001). The area under the curve for the ARFI was 0.91. Conclusions: ARFI has high sensitivity and specificity for identification of thyroid. This technique might be useful to select patients with thyroid nodules for surgery.